Information, Coordination, and the Industrialization of Countries - Florian Englmaier; Markus Reisinger (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
The industrialization process of a country is often plagued by a failure to coordinate investment decisions. Using the Global Games approach we can solve this coordination problem and eliminate the problem of multiple equilibria. We show how appropriate information provision enhances efficiency. We discuss extensions of the model and argue that subsidies may be a property of a signalling equilibrium to overcome credibility problems in information provision. In addition we point out possible problems with overreaction to public information. Furthermore, we suggest a new focus for development policy.
urn:nbn:de:bvb:19-epub-13464-6
Keywords: C72; C79; D82; F21; O12; O14; 330; Information; Coordination; Industrialization; Development; Global Games; Equilibrium Refinements; Big Push